JumpStart deployments in ultra-high-performance optical networking testbeds. - Baldine, Ilia (IEEE Communications magazine)
This article describes deployments of the JumpStart architecture and protocols in several ultra-high-performance optical networking testbeds. JumpStart interoperates with a variety of commercial optical switching gear, and supports operator-, user-, application-, and protocol-initiated ultra-fast lightpath provisioning. We briefly describe JumpStart's data and control plane architectures, and the functionality and performance of its edge and core components. We summarize results from JumpStart testbed demonstrations supporting ultra-fast lightpath provisioning for grids, high-performance file transfers, low-latency zero-jitter interactive visualization, and optical transport using optical burst switching.